2005
DOI: 10.1128/jcm.43.3.1445-1447.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of COBAS AMPLICOR Neisseria gonorrhoeae PCR, Including Confirmation with N. gonorrhoeae- Specific 16S rRNA PCR, with Traditional Culture

Abstract: A total of 3,023 clinical specimens were tested for Neisseria gonorrhoeae by using COBAS AMPLICOR (CA) PCR and confirmation of positives by N. gonorrhoeae-specific 16S rRNA PCR. The sensitivity of CA plus 16S rRNA PCR was 98.8%, compared to 68.2% for culture. Confirmation of CA positives increased the positive predictive value from 54.8 to 96.6%.For the detection of Neisseria gonorrhoeae, culture is still used by many laboratories. However, recent studies showed that nucleic acid amplification-based N. gonorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
13
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
(12 reference statements)
3
13
1
Order By: Relevance
“…There were no culture-positive, NAAT-negative findings. These findings are similar to those of a previous study (10) comparing Cobas Amplicor (AMP) PCR to culture of 3,023 clinical specimens from woman and men, which demonstrated an increase from 58 to 85 positives, an increase of 46% due to PCR testing. Of 142 extra positive samples, 65 were available for confirmatory testing by AGC and 64 (98.5%) were confirmed to be positive.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…There were no culture-positive, NAAT-negative findings. These findings are similar to those of a previous study (10) comparing Cobas Amplicor (AMP) PCR to culture of 3,023 clinical specimens from woman and men, which demonstrated an increase from 58 to 85 positives, an increase of 46% due to PCR testing. Of 142 extra positive samples, 65 were available for confirmatory testing by AGC and 64 (98.5%) were confirmed to be positive.…”
supporting
confidence: 81%
“…Of 142 extra positive samples, 65 were available for confirmatory testing by AGC and 64 (98.5%) were confirmed to be positive. Confirmatory testing of GC Amplicor (AMP)-positive results in a previous study (10) showed a 56.1% rate of confirmation (87/155) using a 16S rRNA N. gonorrhoeae PCR (Roche), and only 57 were culture positive. This lower rate of confirmation may have been due to the AMP PCR crossreacting with nongonorrhoea Neisseria (NGN), a phenomenon which has been widely reported (6,7,17).…”
mentioning
confidence: 99%
“…Still, several cross-reacting nonpathogenic organisms, primarily other Neisseria spp., with homologous sequences are known to contribute to false-positive results (6,7,13,24,25). As recommended by the Centers for Disease Control and Prevention (5), confirmation of N. gonorrhoeae infection using independent testing for a different N. gonorrhoeaespecific target greatly improves the positive predictive value (14).…”
mentioning
confidence: 99%
“…NAAT offers unparalleled specificities and sensitivities, with PCR assays typically boasting sensitivities and specificities of Ͼ95% and 100%, respectively, compared with sensitivities of ϳ68% obtained via culture (3).…”
mentioning
confidence: 99%